Does the nature of a recession matter?: some calculations on fiscal multipliers - Borsoi, Nicolas da Silva (2018)
The existing literature measuring the magnitude of the fiscal multiplier has a considerable consensus that the stimulative effects of fiscal instruments depends on the current state of economic activity, whether it is expanding or facing a recession. However, none of the previous works studied how the source of an economic downturn, if the economy is facing an adverse supply/demand shock, affects the effectiveness of fiscal expansions. We introduce in a simple New Keynesian model with a rich description of fiscal policy, the assumption of imperfectly informed policymakers (fiscal and monetary) to approach the question. Our results point out the existence of disparate effects of fiscal policy depending on whether the economy is facing a demand or a supply recession. Yet, we find out that cuts in taxes are an effective tool to counter the effects of adverse shocks on economic activity and aggregate consumption.